Investigation into steam generator tube life expectancy affected by SFR transients. (January 2022) - Pathak, S.P.; Velusamy, K.; Pandey, S.K.; Kumar, V.A Suresh
Abstract: One of the decay heat removal systems in sodium cooled fast reactors (SFR) is the operation grade decay heat removal system (OGDHRS). During deployment of OGDHRS, steam generator has to operate at off-normal operating conditions which may lead to serious concerns with respect to flow stability in steam generator and the associated thermal fatigue on the tubes. Towards understanding this, tests are performed on a 19-tube once through steam generator simulating two OGDHRS deployment schemes. The consequent fatigue damage assessment of steam generator tubes is carried out using Finite Element Method based commercial software and RCC MR French design code. The fatigue damage fraction is estimated to be∼0.06 suggesting the acceptability of both the schemes for future Indian SFR. The effects of dry-out point temperature oscillation amplitude and its frequency on tube life are also studied. It is found that the oscillation frequency doesn't have much influence on the stress/strain range. It is further found that an increase in oscillation amplitude leads to a near linear increase in the stress range. Highlights: Tests were conducted on a 19-tube sodium-heated once-through steam generator. Two schemes for OGDHRS deployment, viz., at normal and at reduced SG pressures studied. Fatigue damage to SG tubes was predicted by FEM using the measured data. Tube life expectancy is predicted for tube-tube sheet weld joint and dry-out point. Acceptability of both the schemes for future Indian SFR was confirmed. Effects of frequency/amplitude of thermal oscillations on fatigue life are established.